Influence of digital rural construction on farmland transfer contract extension of transfer-out households and mechanism - SI Ruishi, ZHOU Shilei (Ziyuan Kexue)
[Objective] Digital rural construction provides a new opportunity for maintaining the stability and development of the farmland transfer market, and it is of great significance to explore its impact on farmland transfer contract extension of transfer-out households and its mechanism for securing the stability of farmland management right, promoting land management at appropriate scales, and accelerating the modernization of agriculture and the countryside. [Methods] Based on the data of 457 farmland transfer-out households in Shaanxi, Ningxia, and Gansu in 2022, this study constructed an indicator system for digital rural construction from the three aspects of digital technology accessibility, applicability, and availability, and employed the Double Hurdle model and the instrumental variable method to empirically analyze the influence of digital rural construction on farmland transfer contract extension of transfer-out households and mechanism. [Results] Transfer-out households who are willing to extend the contract accounts for 57.77% of the surveyed households, and the average extension period is 3.45-5.98 years. (2) Digital rural construction has a positive effect on transfer-out households’ contract extension willingness and extension period, and this result is still robust after the endogeneity and robustness tests. (3) Heterogeneity analysis showed that digital rural construction has an inverted U-shaped influence on the contract extension period at different quantiles. Meanwhile, the promotion effect of digital rural construction on contract extension is more obvious in the samples with junior high school and above education. Type II and above part-time types, and formal contract signing. (4) Mechanism analysis indicated that digital rural construction mainly promotes contract extension by improving the quality of non-agricultural employment, enhancing the understanding of contract extension, and reducing the contract extension cost. [Conclusion] Strengthening the digital rural construction and activating the potential of digital elements is an important way to promote the farmland transfer contract extension of transfer-out households. We recommend to accelerate the construction of digital rural systems, cultivating new forms of digital economy development, building an information platform for farmland transfer, and improving the regulatory mechanism for farmland transfer contract extension.